USE OF PEDAGOGICAL AND MODERN INFORMATION TECHNOLOGIES IN THE THEORY OF PHYSICAL EDUCATION - A. Makmutaliev (Zeta Repository, 2023)
Today, the role of modern, advanced pedagogical and Information Technology in educating students is very important. In fact, modern, advanced pedagogical technologies in education increase the productivity of the educational process, form the creative thinking process of students. In a word, modern advanced pedagogical technologies, firstly, provide students with the opportunity to improve their knowledge, skills and abilities, and secondly, they contribute to the professional growth, spiritual development of the student as well. The article explores the issues of introduction of pedagogical and information technologies in the science of physical education theory.